Risk-Return Measurement in Portfolio Selection and Performance Appraisal Models: Progress Report - Bower, Richard S.; Wippern, Ronald F. (Journal of Financial and Quantitative Analysis, 1969)
Richard S. Bower, Ronald F. Wippern, Risk-Return Measurement in Portfolio Selection and Performance Appraisal Models: Progress Report, The Journal of Financial and Quantitative Analysis, Vol. 4, No. 4 (Dec., 1969), pp. 417-447